Ambiguous Authority: Juan de Frías and the Audiencia of Santo Domingo Confront the Conquistador Antonio Sedeño (1537). Issue 4 (31st August 2017) - Perri, Michael
Abstract : On May 19, 1537, in a region of the Pearl Coast, two armed factions of Spaniards challenged one another on the banks of the Unare River in what would become eastern Venezuela (seeFigure 1 ). Licenciado Juan de Frías and his smaller force of about 80 men confronted a large party under the command of the conquistador Antonio Sedeño. Frías professed to represent the crown by charge of the Real Audiencia of Santo Domingo, which had bestowed on him a vara del rey (staff of the king, symbolizing royal authority) and sent him off to arrest Sedeño. Sedeño likewise maintained that he had royal authority, citing his capitulación (contract of conquest) for the nearby island of Trinidad and letters from Empress Isabel, wife of Holy Roman Emperor Charles V (King Charles I of Spain) and regent of Spain from 1529–32 and 1535–39. In their confrontation, both Frías and Sedeño claimed to represent the will of the king.